Formation Processes and Morphological Characteristics of Concomitant Occurrence of Malignant Neoplasms and Pulmonary Tuberculosis - qizi Iskandarovа Iroda Mashrabjon (American Journal of Bioscience and Clinical Integrity, 2024)
This article discusses the formation processes and morphological features of the simultaneous presence of malignant tumors and pulmonary tuberculosis. The paper examines the mechanisms that contribute to the development of these diseases in their combined presence, as well as describes the characteristic morphological changes in tissues. The analysis provides a deeper understanding of the interaction between malignant neoplasms and pulmonary tuberculosis, which can contribute to the development of more effective methods of diagnosis and treatment.